Analisi Peran Pemuda dalam Penanggulangan Kemiskinan di Medn Bagian Utara (Studi Kasus: Kecamatan Medan Marelan, Medan Deli, Medan Labuhan, dan Medan Belawan) - Haris Sucipto; Zulkifli Nasution; Mukhlis (Sekolah Tinggi Agama Islam Sumatera Medan, 2017)
This descriptive correlation research analyze the role of youth in handling poverty in the northern part of Medan (Medan Marelan, Medan Deli, Medan Labuhan, and Medan Belawan Subdistricts). The objective of the resesarch was to analyze the role of youth and its influence on handling poverty in the northern part of Medan. The Research used quantitative survey method. The Population was 167,629 people and 96 of them were used as the samples. The results of the research showed that the role of youth in handling poverty in the northern part of Medan was positive, and as leadership, enterprenuership, and pioneering simultaneously had positive influence on poverty in the aspect of welfare. Partially, the variables of leadership and entrepreneurship had positive and significant influence on handling poverty in the aspect of welfare, While pioneering had positive but insignificant influence on handling poverty in the aspect of welfare.